Estudo sobre o impacto da proficiência individual em competências gerenciais no desempenho organizacional de uma instituição financeira de grande porte - Bullara, Rodolfo Furtado de Carvalho (2017)
The pressure for managerial results are increasing continuously. This mandates managers to develop stronger proficiency in competencies (knowledge, skills and attitudes) which are needed to achieve ever more aggressive objectives. On the other hand, the company needs to measure not only if their managers are achieving their strategic objectives, but also how they achieve their results. This is what is expected from an organization's performance appraisal system. The objective of the present study was to determine if, and to what extent, the level of individual proficiency in six managerial competencies influences the effective performance of the branches which they manage in one of the largest brazilian commercial banks. For this, the study verified whether the proficiency of these six competencies influenced the effectiveness of the performance of the branches managed by the subjects. The data was obtained from real performance evaluations. The results clearly indicate that proficiency in managerial competencies was not linked to organizational performance as measured from the branches performance system. The proficiency in the ownership competence had an irrelevant impact on the final evaluation of the branches and its subcomponents. All other competencies also did not show a significant influence on the branches performance scores, indicating that the organizational performance was determined by other factors not measured in this study. As the results contradict previous studies in Brazil and abroad, this paper discusses its important implications in theory and practice of people management and performance, especially regarding performance evaluation based in competencies and its relationship with remuneration practices and career management organizations.